Kinetic parameters of polymer degradation by SAPO-37 - Fernandes, V. J.; Araujo, A. S.; Fernandes, GJT; Matos, JR; Ionashiro, Massao [UNESP] (Springer, 2001)
High density poly(ethylene) has been submitted to thermal degradation alone, and in the presence of silicoaluminophosphate SAPO-37. The processes were carried out in a reactor connected on line to a gas chromatograph/mass spectrometer in order to analyze the evolved products. Polymer degradation was also evaluated by thermogravimetry, from room temperature until 800 degreesC, under nitrogen dynamic atmosphere, with multiple heating rates. From TG curves, the activation energy related to degradation process was calculated using the Flynn and Wall multiple heating rate kinetic model for pure polymer (PE) and for polymer in the presence of catalyst (PE/S37). SAPO-37 showed good selectivity for low molecular mass hydrocarbons in PE catalytic degradation.
Keywords: Flynn and Wall kinetic model; poly(ethylene) degradation; SAPO-37